Work–life tension and its impact on the workforce participation of Australian mothers - Losoncz, I; Graham, B (My University, 2010)
This paper expands on earlier work by Losoncz and Bortolotto (2009), which identified six distinctive groups of working mothers using six waves of the HILDA survey. The focus of this paper is on the labour market behaviour of working mothers in each cluster, and whether reducing working hours or leaving the workforce has benefits for the health and wellbeing of mothers in each cluster, particularly those experiencing high conflict between work and life. Mothers from clusters with high work–life conflict did not show a higher tendency to exit from paid work than mothers from other clusters. The most likely to exit paid work were mothers who had lower regard for the working mother role. As such, role preference seems to have a greater influence on work decisions. Leaving work or reducing hours did not lead to improved satisfaction with family life or parenthood in any of the clusters, while in some clusters, leaving work or reducing hours improved mental and physical health. Policies that promote greater work–life balance may have a different level of influence on mothers’ workforce participation based on their level of work role identification and particular events in their life course.
Australian Social Policy
Keywords: Families; Employment -- Work/life Balance; Families -- Mothers; Employment; Families and relationships; Labour market; Employment; Families; Work/life Balance; Mothers; Families and relationships; Employment and unemployment